Demorest's Family Magazine - Demorest, William Jennings (New York: W. J. Demorest, 1891)
Demorest's Family Magazine. April 1891. Vol. 27, No. 6. -- Republics of America -- The River of Pearls -- The Care of Palms in the Drawing-Room -- How Art Students Live in New York -- Physical Culture -- Kite-flying -- A Hero Worshiper -- Inexpensive Homes -- Larry -- Our Portrait Gallery -- Home Art and Home Comfort -- Grotesque Decorations for Easter Eggs -- Sanitarian -- Kindergarten Work and Play for the Home -- Our Girls -- Artistic Notes -- The World's Progress -- Chat -- What Women are Doing -- Mirror of Fashions -- The Folly and Fallacy of License -- Unconstitutional
Mme Demorest's Mirror of Fashions
New York Illustrated News
Digitized from original print, Valdosta State University Archives and Special Collections, April 6, 2017.
Keywords: Magazine; Illustrated Periodicals; Periodicals; Travel; Dressmaking; Homemaking; Needlework; Women; Catalogue; Children; Social History; Women's History; Fashion; United States; 1800s; 19th Century